2014
DOI: 10.1587/elex.11.20142006
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Si surface flatness to realize high-performance Si devices utilizing ultrathin films with new material system

Abstract: The importance of Si surface flatness on metal-oxide-semiconductor field-effect transistor (MOSFET) characteristics with ultrathin hafnium oxynitride (HfON) high-k gate insulator formed by electron cyclotron resonance (ECR) plasma sputtering was described. The surface roughness of Si substrate was reduced by Ar/4.9%H 2 annealing utilizing conventional rapid thermal annealing (RTA) system. Si surface root-mean-square (RMS) roughness was well controlled by changing the annealing temperature from 700 to 1000°C. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 42 publications
(44 reference statements)
1
21
0
Order By: Relevance
“…The nitrogen concentration in HfON layer was approximately 10%. The EOTs of HfON layer were 0.98 nm for the sample without (w/o) annealed, and 0.78 nm for the sample with Ar/4.9%H2 annealed, respectively [24,26]. Finally, the contact hole was patterned and Al electrodes were formed for gate (G) and S/D by thermal evaporation.…”
Section: Variability Improvement By Si Surface Flattening Of Electricmentioning
confidence: 99%
See 3 more Smart Citations
“…The nitrogen concentration in HfON layer was approximately 10%. The EOTs of HfON layer were 0.98 nm for the sample without (w/o) annealed, and 0.78 nm for the sample with Ar/4.9%H2 annealed, respectively [24,26]. Finally, the contact hole was patterned and Al electrodes were formed for gate (G) and S/D by thermal evaporation.…”
Section: Variability Improvement By Si Surface Flattening Of Electricmentioning
confidence: 99%
“…We have reported that the Si(100) and Si(110) surfaces were able to be flattened by Ar/4.9%H2 annealing utilizing conventional rapid thermal annealing (RTA) system [24]. The annealing was carried out at 700-1000 o C for 60 min, and minimum surface roughness was obtained when the annealing temperature was 1000 o C [24].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have reported various Hf-based high-k gate insulators and also in-situ formation of HfN x (x < 1:0) gate electrode on the Hf-based high-k gate insulator [10,11,12,13,14]. It was found that the in-situ formation of HfN x (x < 1:0) gate electrode improved the electrical characteristics of Hf-based high-k gate insulator [13].…”
Section: Introductionmentioning
confidence: 97%